Evaluating the Implementation of UNGPs on Business and Human Rights: Insights from Indonesia and Vietnam - Uz Zaman, Muhamad Nafi (VNU Journal of Science: Legal Studies; Vol 42 No 2DO - 10.25073/2588-1167/vnuls.4795, 2026)
The development of the paradigm of responsibility for human rights makes corporations actors who should be accountable and held accountable for their activities in addition to the state. In line with the expansion of human rights actors, the United Nations (UN) released the UN Guiding Principles on Business and Human Rights (UNGPs on BHR), which serve as global guidelines for corporations to position themselves as human rights actors. This principle also underpins standardizing regulations on the relationship between business and human rights and calls on governments and corporations to identify, prevent, mitigate, and provide remedies for actual and potential adverse human rights impacts. However, the principle is a soft law that is non-legally binding, which hampers human rights enforcement against corporations, especially in countries that do not ratify it. This article aims to review and evaluate the implementation of the UNGPs on BHR principles in Indonesia and Vietnam. This research uses a doctrinal legal research method and examines literature and secondary data to analyze the legal framework and its implementation. The results of this study show a not-so-significant gap between the UNGPs on BHR principles and the implementation practices in Indonesia and Vietnam. Both countries have committed to adopting the principles into their national legislation and concretizing them in the National Action Plan, which is a real manifestation of both countries' commitment to advancing the values of respect for human rights in business activities.